2020
DOI: 10.1002/ejoc.202000441
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Harvesting Supramolecular Polymers: Energy Transfer to Various Polyaromatic Acceptors

Abstract: https://haener.dcb.unibe.ch/ Supporting information for this article is given via a link at the end of the document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…To date supramolecular nanostructures based on chromophores, such as perylenes [100,101], cyanines [15,43,94,102,103], phenanthrenes [104,105], porphyrins [88], HBC [59] and CBT [55,68] (see also figure 3), are reported to sustain long-range transport. These building blocks were self-assembled into elongated (hierarchical) nanostructures such as NFs, nanotubes and double-walled nanotubes.…”
Section: General Aspects Of Long-range Energy Transport In (Individua...mentioning
confidence: 99%
See 1 more Smart Citation
“…To date supramolecular nanostructures based on chromophores, such as perylenes [100,101], cyanines [15,43,94,102,103], phenanthrenes [104,105], porphyrins [88], HBC [59] and CBT [55,68] (see also figure 3), are reported to sustain long-range transport. These building blocks were self-assembled into elongated (hierarchical) nanostructures such as NFs, nanotubes and double-walled nanotubes.…”
Section: General Aspects Of Long-range Energy Transport In (Individua...mentioning
confidence: 99%
“…These building blocks were self-assembled into elongated (hierarchical) nanostructures such as NFs, nanotubes and double-walled nanotubes. In those nanostructures, transport distances of some 100 nm, up to about 800 nm, have been demonstrated either by direct microscopic PL imaging (figures 14(a) and (b)) [88,94,100,106], by indirect exciton-exciton annihilation [102] or sensitizing experiments [104,105,107]. Still longer transport distances were reported by Caram et al [15] who showed via annihilation measurements distances of (1.6 ± 1.0) μm in C8S3-based J-type doublewalled nanotubes stabilised in a sugar-based matrix.…”
Section: General Aspects Of Long-range Energy Transport In (Individua...mentioning
confidence: 99%
“…Although this energy funnel is not reversible, it inspired synthetic approaches. For instance, appending several chemically distinct chromophores to a DNA scaffold 16,17 or doping one-dimensional supramolecular nanostructures with acceptor molecules 18,19 predefines the direction for energy transfer. Control of energy transport by external stimuli was shown in organic single crystals 20 and hybrid systems 21 by applying an electric field or by introducing a local strain gradient with an atomic force microscope tip that creates local topological quenchers.…”
Section: Introductionmentioning
confidence: 99%
“…9 In particular, the employment of water as a medium opens the possibility of using highly polar and even ionic compounds as building blocks for the assembly of supramolecular systems. Supramolecular polymers assembled in aqueous medium find applications in biomedical engineering, 2,[9][10][11][12][13][14][15][16] sensing, 17 organic electronics, 18 light harvesting [19][20][21][22][23] and solar energy conversion. 9,24 For the assembly of supramolecular structures with special spectroscopic and light-harvesting properties, p-conjugated and aromatic molecules are of particular interest.…”
mentioning
confidence: 99%
“…2,9 We have previously observed light-harvesting properties in various types of supramolecular assemblies of oligophosphates based on phenanthrenes and tetraphenylethylene in aqueous medium. [19][20][21]25 Further, pyrene trimers showed interesting spectroscopic properties due to their selfassembly into nanosheets. 26 These polyaromatic oligomers were joined by phosphodiester linkages and, thus, were of anionic nature.…”
mentioning
confidence: 99%